Community Roles in Managing Coastal Tourism: A Case of Labuhan Haji Beach, East Lombok - Muhammad Adi Junaidi; Evilia Rochmi; Amrullah; Muhamad Juaini (Sumber Belajar Sejahtera, 2026)
This study aims to analyze the role of local communities in the management of community-based tourism (CBT) in Labuhan Haji Beach, East Lombok, as well as identify challenges and strategies to strengthen this role in supporting the sustainability of coastal tourism. The method used is a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observations, and documentation studies. The informants consisted of Pokdarwis administrators, tourism business actors, village governments, and domestic tourists. The results of the study show that local communities play a role in four main aspects: (1) destination operational management (cleanliness, security, tourism services), (2) environmental and cultural preservation, (3) local economic development through diversification of tourism businesses, and (4) participation in local institutions, especially through Pokdarwis. Apart from this, the level of community participation is still at the consultative and functional level, not yet achieving strategic partnerships in decision-making. The main challenges include weak human resource capacity, limited capital, unstable Pokdarwis institutions, lack of infrastructure, and not optimal digital promotion of destinations. This study recommends strengthening strategies through community capacity building, inclusive co-management models, development of cultural and ecological-based tourism products, and marketing digitalization. These findings contribute to strengthening the implementation of CBT in coastal areas as well as practical implications for governments and tourism stakeholders.